Low-Voltage Electrical Installations : (IEC, 2010)
The particular requirements of this part of IEC 60364 apply to electrical installations of: - basins of swimming pools and paddling pools and their surrounding zones; - areas in natural waters, lakes in gravel pits and coastal and similar areas, specially intended to be occupied by persons for swimming, paddling and similar purposes, and their surrounding zones. Such areas in natural waters, lakes in gravel pits and coastal and similar areas, are considered as swimming pools; - basins of fountains and their surrounding zones